Volumetric Extraction of Pulmonary Blood Vessels from Computerized Tomography Scans - (:unkn) unknown (IEEE, 2018)
In this study we created 3D model of pulmonary blood vessels in order to help surgeons while they are performing bronoschopy which is for cancer detection on early stages and preventing unintended interception to blood vessels during process. From Computerized Tomography scans, masks are created by using morphological operations which are used to segment lungs and blood vessels. Segmented blood vessels then shown in 3D space by relation of their pixel intensities.
Keywords: Pulmonary Computerized Tomography; Blood Vessel Segmentation; Biomedical Image Processing; Pattern Recognition